Optimal Pricing and Extended Warranty Strategies for Maximizing Profit in (Re)manufacturing With Customer Returns and Production Recovery - M. Mubashir Unnissa; D. Kalpanapriya; P. Jalapathy (IEEE Access, 2025)
The management of remanufacture products has become an essential focus for Original Equipment Manufacturers, driven by the economic benefits associated with these products and the increasing global emphasis on sustainability. In this context, pricing and extended warranty strategies function as control mechanisms within (re)manufacturing management. These strategies facilitate the adjustment of demand for both new and reman products, while also addressing potential market share cannibalization between these two product categories. This paper presents a mathematical model designed to explore optimal production and pricing strategies, incorporating considerations of extended warranty for a monopolistic manufacturer engaged in (re)manufacturing. The model takes into account convex collection and inspection costs, employs two quality bins for product returns, and recognizes (re)manufacturing losses. The derivation of optimal production and pricing strategies when offering an extended warranty is accomplished through the resolution of a convex programming model. Our findings outline the circumstances under which the manufacturer should prioritize the production of new products, reman products, or a combination of both. Additionally, numerical experiments are conducted to assess the sensitivity of the optimal strategies, thereby providing further managerial insights.